Detection, Occurrence and Fate of Emerging Contaminants in Agricultural Environments. (1st October 2013) - Snow, Daniel D.; Cassada, David A.; Papastavros, Efthimia; Bartelt–hunt, Shannon L.; Li, Xu; Zhang, Yun; Zhang, Yuping; Yuan, Qi; Sallach, J. Brett
Abstract : A total of 62 papers published in 2012 were reviewed ranging from detailed descriptions of analytical methods, to fate and occurrence studies, to ecological effects and sampling techniques for a wide variety of emerging contaminants. New methods and studies on veterinary pharmaceuticals, steroids, antibiotic resistance genes and prion proteins in agricultural environments continue to expand our knowledge base on the occurrence and potential impacts of these compounds. This review is divided into the following sections: Introduction, Analytical Methods for Emerging Contaminants, Monitoring with Passive Samplers, Occurrence and Fate of Steroid Hormones, Antimicrobials and Antibiotic Resistance Genes, and Prions as Emerging Contaminants.